Traceability and Management Information Techniques of Agricultural Product Quality Safety in China - Xinting, Yang; Ming, Li; Chuanheng, Sun; Jianping, Qian; Zengtao, Ji (Recent Patents on Computer Science, 2012)
Agricultural product quality safety is one of the hot topics in the world. From the technical view, the agricultural production management and traceability are the key measurement for insuring the quality safety. The paper introduced the research progress of traceability systems, and also discussed relevant patents. From 2005 until now, based on long-term requirement investigation and analysis, we have been investigating the system architecture for the data flow of information service for agricultural product quality safety, and developed six techniques, four equipments and six kinds of information systems. The six techniques include individual identification and coding, barcode generating and printing middleware, barcode encryption and decryption, RFID middleware, GAP-based (good agricultural practices) early warning, and XML-based data transferring. The four equipments are portable real-time record-keeping equipments for agricultural production, portable intelligent dispatching equipments for agricultural products, portable supervision equipments for agricultural products, and control equipments for agricultural product sale. The six kinds of information systems are environmental evaluation systems for agricultural fields, management information systems for agricultural safe production, wholesale market management system, logistics management system, agricultural product quality safety supervision and traceability systems and emergency management systems for agricultural product quality. Until October 2011, we have applied the above techniques to aquatic products, vegetables and fruits, as well as livestock traceability in Beijing, Tianjin, and Guangdong, China. The application has gained significant economical, social and ecological benefits.
Keywords: management information system